Characterization of Biosurfactants from Endophytic Bacteria Isolated from Geothermal Fern Leaves D9 - Shobakhatun Nur Fadilla; Bambang Cahyono; Agustina L. N. Aminin (Jurnal Kimia Sains dan Aplikasi, 2026)
Biosurfactants are surface-active compounds synthesized by microorganisms. These compounds offer several advantages, including low toxicity, high compatibility, and biodegradability. Biosurfactants can be isolated relatively quickly, a property that renders them potentially applicable in industrial settings. One type of microorganism that produces biosurfactants is endophytic bacteria, which live within plant tissues. The present study focuses on the characterization of biosurfactants produced by endophytic bacteria isolated from geothermal ferns in the area around the Gedong Songo hot spring in Semarang Regency. Isolate 9 (D9) demonstrated the optimal oil-spreading capability and was consequently selected for further production and characterization. The optimal growth curve for biosurfactant production by isolate D9 (BS-D9) occurred in the early stationary phase, approximately 132 hours post-inoculation, with an oil-spreading diameter of 5.1 centimeters. The emulsification index (E24) of BS-D9 reached 95%, which is nearly equivalent to SDS at 1000 ppm, suggesting a high emulsification capacity. The methylene blue test indicated that BS-D9 is an anionic biosurfactant, whereas the negative Biuret test result indicated that it does not belong to the lipopeptide group. Fourier-transform infrared (FTIR) spectroscopy indicates that BS-D9 falls within the glycolipid category. This classification is supported by a distinctive absorption peak corresponding to glycosidic bonds, potentially of the rhamnolipid type. Rhamnolipids are widely recognized for their high emulsification efficiency, stability, and environmental compatibility, making them attractive for various industrial applications. These results indicate that BS-D9 has potential applications as a surface-active agent with environmentally friendly properties.